2012
DOI: 10.1128/jvi.00023-12
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse Genetics Approach To Study Feline Infectious Peritonitis

Abstract: Feline infectious peritonitis (FIP) is a lethal immunopathological disease caused by feline coronaviruses (FCoVs). Here, we describe a reverse genetics approach to study FIP by assessing the pathogenicity of recombinant type I and type II and chimeric type I/type II FCoVs. All recombinant FCoVs established productive infection in cats, and recombinant type II FCoV (strain 79-1146) induced FIP. Virus sequence analyses from FIP-diseased cats revealed that the 3c gene stop codon of strain 79-1146 has changed to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…In conclusion, the data obtained in this study support the ''internal mutational theory'' rather than the ''circulating virulent/avirulent FCoV'' hypothesis. However, the significance of specific mutation events in the generation of FIPV needs to be further evaluated using reverse genetic systems for both serotype I and II feline coronaviruses followed by animal experiments (Tekes et al, 2008(Tekes et al, , 2010(Tekes et al, , 2012. .…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the data obtained in this study support the ''internal mutational theory'' rather than the ''circulating virulent/avirulent FCoV'' hypothesis. However, the significance of specific mutation events in the generation of FIPV needs to be further evaluated using reverse genetic systems for both serotype I and II feline coronaviruses followed by animal experiments (Tekes et al, 2008(Tekes et al, , 2010(Tekes et al, , 2012. .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas serotype II FCoVs replicate well in feline tissue culture cells in vitro, serotype I FCoVs grow poorly, if at all, in cell culture, except for a few cell cultureadapted isolates. Accordingly, in the last decade, most studies on FCoVs were based on serotype II viruses, while the more prevalent serotype I FCoVs were largely neglected (de Haan et al, 2005;Dye and Siddell, 2005;Haijema et al, 2003Haijema et al, , 2004Rottier et al, 2005;Tekes et al, 2012).…”
Section: Fcov Serotypes and Cellular Receptor Usagementioning
confidence: 99%
“…Despite the existence of serotype I and II FIPVs, the characteristics of the disease caused by these serotypes appear to be very similar. The incubation time for naturally occurring FIP cases is difficult to assess, but a number of studies using experimentally infected specific pathogen-free (SPF) cats revealed incubation times of 2-14 days for the wet form and several weeks for the dry form (Kiss et al, 2004;Pedersen and Black, 1983;Pedersen et al, 1981aPedersen et al, , 1984Tekes et al, 2012). Following experimental infections with the prototype serotype II FIPV 79-1146 strain or a recombinant form of this virus, respectively, cats were shown to develop fever after a few days and lost weight rapidly.…”
Section: Feline Infectious Peritonitis Virusmentioning
confidence: 99%
“…Unfortunately, our mAbs are not well suited to detect the secreted glycosylated form of 7b. To further study the synthesis, intracellular localization and secretion of 7b, we will use our reverse genetics system (Tekes et al, 2008(Tekes et al, , 2012 to obtain recombinant viruses containing the desired changes in the 7b coding sequence. Ultimately, these studies together with the three dimensional structure of 7b will give more insight into the biological role of the 7b protein.…”
Section: Discussionmentioning
confidence: 99%
“…Both cell lines were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal calf serum (FCS), penicillin (100 IU ml À1 ) and streptomycin (100 IU ml À1 ) in 5% CO 2 at 37 C. The type-II strain FCoV 79-1146 was kindly provided by R. J. de Groot, University of Utrecht, The Netherlands (GenBank NC_002306). The recombinant type-I FCoV strain recFCoV-DStop-7b was generated by reverse genetics as described previously (Tekes et al, 2012). It comprises the type-I FCoV strain Black with a restored accessory gene 7b (GenBank EU186072).…”
Section: Viruses and Cellsmentioning
confidence: 99%